Seven heavens? The character and importance of afterlife belief among contemporary Australians. (2nd April 2016) - Singleton, Andrew
Abstract: This article draws on in-depth qualitative interviews with 52 people to examine the meaning and character of afterlife belief among contemporary Australians. It explores the varieties of afterlife belief and considers the impact such beliefs have, particularly in relation to death and dying. The analysis reveals that afterlife belief is varied, individualistic and mainly arrived at with little to no reference to orthodox religious teaching. People variously believe in heaven, reincarnation, life on another plane or something more abstract. Those who follow faithfully a religious tradition are largely ignorant of detailed theological doctrines about life after death and like other kinds of believers, exercise their own authority and judgment over matters of belief.